Duolingo Arabic sebagai Media Inovatif dalam Pembelajaran Maharah Qira’ah: Tinjauan Literatur - Achmad Naufal; Erlina erlina; Umi Hijriyah; Koderi koderi; guntur kesuma (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
This study presents a literature review of the use of the Duolingo Arabic application to develop maharah qira’ah (Arabic reading skills) through the integration of audiovisual and gamified learning approaches. The research used a qualitative literature review, analysing empirical and conceptual studies published between 2015 and 2025 on digital technology and Arabic language learning. Data were obtained from scholarly journals, proceedings, and academic databases such as Google Scholar, DOAJ, and ResearchGate, and analysed using content analysis to identify patterns, themes, and trends regarding the effectiveness of Duolingo Arabic in enhancing reading skills. The findings indicate that Duolingo Arabic significantly improves learners’ vocabulary mastery, literal comprehension, and reading fluency through its interactive audiovisual features and game-based reinforcement system. Moreover, the use of gamification elements such as points, levels, and instant feedback was found to increase learner motivation, engagement, and self-regulated learning behaviour. However, limitations were identified in addressing higher-level reading comprehension, including discourse interpretation and contextual understanding. The study concludes that Duolingo Arabic serves as an effective supplementary tool for foundational and intermediate levels of Arabic reading instruction, aligning with digital literacy frameworks and contemporary language pedagogy. Future research is recommended to empirically examine the long-term effects of AI-driven personalisation in Duolingo on deep reading comprehension